SYMBIOSIS AMONG GOOD BMT GOVERNANCE, ENTITY DURABILITY AND CAPITAL SOCIAL - Padlim Hanif; Fachruzzaman; Madani Hatta; Rara Mianti (RADJA PUBLIKA, 2025)
This research was conducted to determine the management of the sharia entity Baitul Mal Wa Tam Wil Kelompok Usaha Bersama (KUBE) Sejahtera 008. Sharia entity has a good existence as proven by an ownership of assets such as building and land. According to its location, the sharia entity is located in Srikuncoro Village, Central Bengkulu Regency. This location has a strategic position close to the city center so that it is possible for residents of Srikuncoro village, Central Bengkulu Regency to obtain even greater financing services than Baitul Mal Wa Tam Wil Kelompok Usaha Bersama (KUBE) Sejahtera 008. In fact, this sharia entity remains the choice of the people of Srikuncoro Village, even this sharia entity has durability which indirectly becomes its identity. The results showed that the management of Baitul Mal Wa Tam Wil Kelompok Usaha Bersama (KUBE) Sejahtera 008 conforms with the principles of Good Governance such as Transparency, Accountability, Responsibility, Independency, and Fairness. The application of these principles is also greatly helped by the existence of Capital Social such as kinship, deliberation and consensus, tolerance and mutual respect that develop in the Srikuncoro Village community. In addition, the Capital Social makes up durability of Baitul Mal Wa Tam Wil Kelompok Usaha Bersama (KUBE) Sejahtera 008 and also contributes to form interrelation between Good Governance and Entity Durability.